CyTOF Analysis Reveals a Distinct Immunosuppressive Microenvironment in IDH Mutant Anaplastic Gliomas - Fu, Weilun; Wang, Wenjing; Li, Hao; Jiao, Yuming; Weng, Jiancong; Huo, Ran; Yan, Zihan; Wang, Jie; Xu, Hongyuan; Wang, Shuo; Wang, Jiangfei; Chen, Dexi; et al. (Frontiers in Oncology, 2021)
The immune microenvironment is important for the development, progression, and prognosis of anaplastic glioma (AG). This complex milieu has not been fully elucidated, and single-cell analysis is urgently needed. Applying mass cytometry (CyTOF), we analyzed immunocytes from 5 patients with anaplastic astrocytoma, IDH-mutant (AAmut) and 10 patients with anaplastic oligodendroglioma, IDH-mutant and 1p/19q codeletion (AOD) and their matched peripheral blood mononuclear cells (PBMCs). Using a panel of 33 markers, we provide a single-cell view of the complex AG immune microenvironment. Our study confirmed that mononuclear phagocytes and T cells dominate the immune microenvironment of AGs. Glioma-associated microglia/macrophages in both AAmut and AOD showed highly immunosuppressive characteristics. Compared to those in the PBMCs, the proportions of exhausted CD4+ and CD8+ T cells were higher at the AG tumor sites. The immune microenvironment in AAmut exhibits more inhibitory characteristics than that in AOD.